Multitoric surfaces and Euler obstruction of a function - Dalbelo, T. M. [UNESP]; Pereira, M. S. [UNESP] (World Scientific Publishing, 2016)
In this work, we present a formula to compute the Euler obstruction of a function f: (X, 0) → (C, 0) and its Brasselet number, where X is a multitoric surface. As an application of this formula, we compute the Euler obstruction of a function on some families of determinantal surfaces.
Keywords: Brasselet number; determinantal surfaces; Euler obstruction of a function; Multitoric surfaces